Concomitant Annular Enlargement in Minimally Invasive Aortic Valve Replacement. Issue 2 (April 2019) - Robinson, Davida A.; Johnson, Carl A.; Goodman, Ariana M.; Knight, Peter A.
Objective: Aortic root enlargement may be necessary to implant adequately sized valves to avoid patient–prosthetic mismatch. Our objective was to assess the feasibility of annular enlargement during aortic valve replacement via a right anterior minithoracotomy. Methods: Twelve consecutive patients undergoing elective minimally invasive aortic valve replacement requiring annular enlargement over a 2-year period were retrospectively reviewed. A right anterior minithoracotomy was performed in all patients. Cardiopulmonary bypass and aortic crossclamp times, hospital length of stay, postoperative complications, rate of reoperation, echocardiographic data, and mortality were analyzed. Results: Mean age was 66 years ± 14. Mean body mass index was 34 ± 7.8 kg/m 2 . All patients had normal preoperative ejection fractions. Indications for aortic valve replacement were severe (3/12, 25%) or critical (9/12, 75%) aortic stenosis due to degenerative aortic valve disease (10/12, 83%) and congenitally bicuspid aortic valve (2/12, 17%). Cardiopulmonary bypass and aortic crossclamp times were 144.7 ± 14.7 minutes and 111.7 ± 10.6 minutes, respectively. The median postoperative length of stay was 4 days. Peak and mean aortic valve gradients on postreplacement intraoperative transesophageal echocardiography were 14.5 ± 9.4 mmHg and 7.2 ± 4.2 mmHg, respectively, with no perivalvular leak on intraoperative or follow-up transthoracic echocardiogram. Postoperative transthoracic echocardiography had peak and mean aortic valve gradients of 12.1 ± 6.9 mmHg and 6.3 ± 3.7 mmHg, respectively. There were no postoperative mortalities. Freedom from reoperation was 100%. Conclusions: Annular enlargement performed during minimally invasive aortic valve replacement is feasible. Basic minimally invasive skills are recommended prior to instituting these more advanced techniques.